Pengaruh Earning Per Share, Price Earning Ratio, dan Return On Asset Terhadap Harga Saham Pada Bank Dengan Kategori Buku IV Periode 2013-2020 - Noor Laila; Sugiharto; Noor Hidayanti (Smart Business Journal (SBJ), 2022)
This study aims to determine and examine the significant effect partially and simultaneously between Earning Per Share (EPS), Price Earning Ratio (PER), and Return On Assets (ROA) on Stock Prices in Book IV category banks for the 2013-2020 period. This research is a research with quantitative approach method and with explanatory research type. The population in this study were all bank financial statements in the Book IV category. The sample used is the financial statements of PT. Bank Rakyat Indonesia, tbk, PT. Bank Negara Indonesia, tbk, PT. Bank Mandiri, tbk, and PT. Bank Central Asia, tbk period 2013-2020. The sampling technique used is purposive sampling. Data collection techniques with documentation methods and data analysis techniques used in this study using Multiple Linear Regression Analysis. The results of this study prove that Earning Per Share (EPS) has a significant partial effect on stock prices with a sig value of 0.000 <0.05 and an effective contribution value of 45.7%, Price Earning Ratio (PER) has a significant partial effect on stock prices. With a sig value of 0.000 <0.05 and an effective contribution value of 38.9%, the Return On Assets (ROA) partially has no significant effect on stock prices with a sig value of 0.075 > 0.05 and an effective contribution value of 3.6 %, and Simultaneously Earning Per Share (EPS), Price Earning Ratio (PER), and Return On Assets (ROA) have a significant effect on stock prices with a sig value of 0.000 <0.05 with a magnitude of effect of 88.2%